Computational methods and algorithms for medicine and optimized clinical practice - Chui, Kwok Tai; Lytras, Miltiadis D. 1973- (IGI Global, 2019)
"This book examines applied and theoretical aspects of industrial engineering and related areas. It also explores empirical and theoretical research on the development, improvement, implementation, and evaluation of integrated systems in engineering"--Provided by publisher